2,4-Dioxochroman Moiety Linked to 1,2,3-triazole Derivatives as Novel α-glucosidase Inhibitors: Synthesis, In vitro Biological Evaluation, and Docking Study - Mollazadeh, Marjan; Mohammadi-Khanaposhtani, Maryam; Valizadeh, Yousef; Zonouzi, Afsaneh; Faramarzi, Mohammad A.; Hariri, Parsa; Biglar, Mahmood; Larijani, Bagher; Hamedifar, Haleh; Mahdavi, Mohammad; Sepehri, Nima (Current Organic Chemistry, 2020)
In this study, a novel series of 2,4-dioxochroman-1,2,3-triazole hybrids 8a-l was synthesized by click reaction. These compounds were screened against α-glucosidase through in vitro and in silico evaluations. All the synthesized hybrids exhibited excellent α-glucosidase inhibition in comparison to standard drug acarbose. Representatively, 3-((((1-(3,4-dichlorobenzyl)-1H-1,2,3-triazol-4-yl)methyl)amino)methylene)chroman-2,4- dione 8h with IC50 = 20.1 ± 1.5 μM against α-glucosidase, was 37-times more potent than acarbose. Enzyme kinetic study revealed that compound 8h was a competitive inhibitor against α-glucosidase. In silico docking study on chloro derivatives 8h, 8g, and 8i were also performed in the active site of α -glucosidase. Evaluations on obtained interaction modes and binding energies of these compounds confirmed the results obtained through in vitro α-glucosidase inhibition.
Keywords: 1; 2; 3-Triazole